Genetic diversity of Ralstonia solanacearum, A phytopathogenic bacterium infecting horticultural plants in Java, Indonesia - NIARSI MERRY HEMELDA; RAMADHANI SAFITRI; SONY SUHANDONO (Biodiversitas Journal of Biological Diversity, 2019)
Hemelda NM, Safitri R, Suhandono S. 2019. Genetic diversity of Ralstonia solanacearum, A phytopathogenic bacterium infecting horticultural plants in Java, Indonesia. Biodiversitas 20: 364-372. Ralstonia solanacearum is a phytopathogenic bacterium causing bacterial wilt disease which has been reported to infect many important plants in Indonesia. However, less study has been done on its genetic diversity in Indonesia. This study aimed to investigate the genetic diversity of R. solanacearum virulent strains isolated from Java Island. BOX-PCR fingerprint was carried out to investigate the genetic pattern of R. solanacearum isolates, while phylogenetic analysis of mutS gene was performed to determine the genetic diversity of R. solanacearum isolates. A total of 21 isolates was obtained from four crop species: twenty isolates identified as phylotype I while one isolate identified as phylotype II. Based on BOX-PCR, most of the isolates clustered according to their original provinces, indicating site-dependent distribution pattern. However, BOX-PCR also detected site-contaminations indicated by the similar genetic patterns found in two provinces. Phylogenetic analysis of mutS gene discovered that most of the phylotype I isolate showed 100% similarity to each other, while phylotype II isolate belonged to phylotype IIB and showed 100% similarity to IPO1609 strain. Pathogenicity and biovar test were confirmed that the phylotype IIB isolate belonged to the R3bv2 strain which was adapted in low temperature. This study provided the first description about genetic diversity patterns of R. solanacearum strains in Java Island and revealed new challenges related to how to prevent contamination of R. solanacearum from one province to another, as well as the phylotype IIB strain infection in a highland area in Indonesia.